1981
DOI: 10.1007/bf01907776
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and regional myocardial responses to AR-L 115 BS, a positive inotropic imidazo-pyridine, in the absence or in the presence of the bradycardiac action of alinidine

Abstract: SummaryThe effects of the imidazo-pyridine AR-L 115 BS on global and regional myocardial function were investigated in anesthetized pigs in the absence and in the presence of the bradycardiac action of alinidine. AR-L 115 BS (0.1-0.8 mg 9 kg -1 9 rain -1) increased myocardial contractility (up to 75 %) and reduced preload (50 %) and afterload (50 %) in a dose-dependent manner. These changes were accompanied by moderate increases in heart rate (up to 20 %). The increase in cardiac output was only moderate (20 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Yet AR-L directly activates the myofibrils in a concentration range close to the plasma concentrations of AR-L 115BS associated with positive inotropic effects in intact pigs (Verdouw et al, 1981). Effects of AR-L on cardiac cell membranes have not been studied extensively, but there are data showing that AR-L 115BS enhances the process of Ca ++ -induced Ca ++ release in mechanically skinned heart muscle cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Yet AR-L directly activates the myofibrils in a concentration range close to the plasma concentrations of AR-L 115BS associated with positive inotropic effects in intact pigs (Verdouw et al, 1981). Effects of AR-L on cardiac cell membranes have not been studied extensively, but there are data showing that AR-L 115BS enhances the process of Ca ++ -induced Ca ++ release in mechanically skinned heart muscle cells.…”
Section: Discussionmentioning
confidence: 98%
“…In the intact animal, AR-L has a number of effects depending on the dose. Contractility, heart rate, and preload are increased and afterload is decreased (Diederen and Kadatz, 1981;Verdouw et al, 1981). Thus, whereas direct effects of AR-L on the heart appear to be a likely mode of action of the drug, in the intact animal effects of AR-L on cardiac output most likely are the result of a variety of pharmacological actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the echocardiograms was carried out as described elsewhere (5,6). and 150 mg metomidate i.v.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the concomitant decrease in myocardial O2-extraction was caused by an increase in 02-supply due to a coronary vasodilatation and a decrease in O2-demand as a consequence of a reduction in afterload and a negative inotropic action (1)(2)(3)(4). Regional myocardial function was described with the aid of myocardial wall thickness tracings obtained from the same myocardial segment (5,6). O2-consumption of the LAD-perfused area was calculated from the LAD-flow and the difference between the O2-content in the LAD and the great cardiac vein.…”
Section: Introductionmentioning
confidence: 99%